A TEACHERS' CREATIVITY IN THE ERA OF THE 5.0 HAS THE POTENTIAL TO SIGNIFICANTLY ENHANCE STUDENTS' LEARNING OUTCOMES AND ARGUMENTATION SKILLS: A NEEDS ANALYSIS WITH RASCH MODEL - Nababan, Kartyka; Renta, Renta; Tammu, Orpa; Kuendo, Wilce Anna Cahya (Fakultas Ilmu Pendidikan Universitas Negeri Surabaya, 2024)
This research is a preliminary research on the correlation of teacher creativity in the era of 5.0 on chemistry learning achievement and students' argumentation skills which will be continued into a more complete research. The ultimate goal to be achieved from this research is to find out the correlation of teacher creativity on chemistry learning achievement and students' argumentation skills. This research uses a descriptive analysis method, which is research that uses descriptive data results obtained from existing data. This type of research conducted by collecting several sources relevant to the topic discussed in order to obtain valid data to support this research. Teacher creativity during learning is proven to improve chemistry learning achievement and students' argumentation skills. Chemistry is an abstract, real, tiered science and cannot be learned directly, so there needs to be the right technique in learning chemistry. The result of the research showed that the teacher creativity in designing learning, choosing the right methods and media can make it easier for students to understand the material and help students improve their argumentation skills.